Control of cationic nanogel PEGylation in heterogeneous ARGET ATRP emulsion polymerization with PEG macromonomers. Issue 14 (7th May 2018) - Spencer, David S.; Luu, Bryan C.; Beckman, David W.; Peppas, Nicholas A.
ABSTRACT: Crosslinked cationic nanoscale networks with hydrophobic cores are an environmentally robust alternative to self‐assembled polymeric drug delivery carriers with respect to therapeutic encapsulation and stability to dilution. However, the ability to tune the degree of PEG incorporated into nanogels during synthesis is more challenging. In this work, biodegradable cationic nanogels were synthesized by ARGET ATRP emulsion polymerization in a single step. The density of PEG in the final nanogels ranged from zero to 40 wt % and was dependent on the feed concentration of PEG monomer, surfactant concentration, surfactant hydrophilic–lipophilic balance, and the ratio of cationic to nonionic surfactant. A comprehensive analysis of nanogel material properties as a function of PEG graft density is presented including analysis of composition, monomer conversion, thermal properties, size, surface charge, and degradation. This study provides a robust analysis for the synthesis of degradable cationic nanogels via a controlled radical polymerization with predictable degrees of PEGylation. © 2018 Wiley Periodicals, Inc. J. Polym. Sci., Part A: Polym. Chem.2018, 56, 1536–1544 Abstract : Biodegradable cationic nanogels with hydrophobic cores and tunable amounts of surface poly(ethylene glycol) (PEG) were synthesized using a one‐step approach with an ARGET ATRP emulsion polymerization. The amount of PEG incorporated into cationic nanogels was a function of initial PEG macromonomer concentration, surfactant concentration, and surfactant hydrophilic–lipophilic balance. This method provides a robust one‐step approach to the synthesis of PEGylated nanogels without the need for postsynthesis crosslinking or conjugation schemes.